Nighttime Swimming Behavior of a Mesopelagic Fish - Christiansen, Svenja; Titelman, Josefin; Kaartvedt, Stein (Frontiers in Marine Science, 2019)
Nocturnal migration of mesopelagic fish into surface waters is well-documented. Yet, although there is increasing evidence of individual-based deviations from average population migrations and of the importance of small-scale individual behavior for predator-prey interactions and energetic cycling, little is known about what mesopelagic animals do when in upper waters. Using high-resolution data from an upward-facing, moored, split-beam echosounder we analyzed the night-time individual vertical swimming behavior of pearlsides (Maurolicus muelleri) over one winter. The population behavior is characterized by migration to the surface after sunset, “midnight-sinking” and another migration to the surface in the morning, followed by return to the daytime habitat. Focusing on individuals unveiled diverse behavioral patterns during different phases of the migration. After ascending to upper layers at dusk, M. muelleri leaves the surface waters, not by sinking, but by actively swimming in a step-wise pattern characterized by relocations alternated by pauses. Following the descent, vertical swimming is sustained at lower levels. Around midnight, the vertical swimming direction changes from predominantly downwards to upwards. Several hours before dawn, the fish start ascending towards the surface in a step-wise pattern. During population ascent in the afternoon and descent in the morning, some individuals at the fringes of schools migrate without intermittent pauses. This study documents the feasibility of using submerged, stationary echosounders in unveiling the individual behavior of mesopelagic fish.